Improved Stator Flux Estimation for Direct Torque Control of Induction Motor Drives - Yahya Ahmed Alamri; Nik Rumzi Nik Idris; Ibrahim Mohd. Alsofyani; Tole Sutikno (Institute of Advanced Engineering and Science, 2016)
Stator flux estimation using voltage model is basically the integration of the induced stator back electromotive force (emf) signal. In practical implementation the pure integration is replaced by a low pass filter to avoid the DC drift and saturation problems at the integrator output because of the initial condition error and the inevitable DC components in the back emf signal. However, the low pass filter introduces errors in the estimated stator flux which are significant at frequencies near or lower than the cutoff frequency. Also the DC components in the back emf signal are amplified at the low pass filter output by a factor equals to . Therefore, different integration algorithms have been proposed to improve the stator flux estimation at steady state and transient conditions. In this paper a new algorithm for stator flux estimation is proposed for direct torque control (DTC) of induction motor drives. The proposed algorithm is composed of a second order high pass filter and an integrator which can effectively eliminates the effect of the error initial condition and the DC components. The amplitude and phase errors compensation algorithm is selected such that the steady state frequency response amplitude and phase angle are equivalent to that of the pure integrator and the multiplication and division by stator frequency are avoided. Also the cutoff frequency selection is improved; even small value can filter out the DC components in the back emf signal. The simulation results show the improved performance of the induction motor direct torque control drive with the proposed stator flux estimation algorithm. The simulation results are verified by the experimental results.